2014
DOI: 10.15331/jdsm.4134
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Use of Complete Denture Prosthesis as Mandibular Advancement Device in the Treatment of Obstructive Sleep Apnea in Edentulous Subjects

Abstract: Prorated subscriptions are not available. Subscriptions begin with the January issue of the current year. Renewals should be secured as early in the year as possible to avoid uninterrupted service. Questions about subscriptions (including payments, billing procedures, or policy matters) should be directed to the AADSM office at (630) 737-9705.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…In accordance with the limitations of this study, the following conclusions were drawn: The overall incidence of OSA in elderly edentulous patients was found to be 40.94% (32.03% male, 8.91% female). An inverse correlation between OSA severity (as estimated by AHI, RERA, and RDI scores) and serum serotonin level was validated in this study. Use of complete dentures modified to function as MAD led to a reduction in AHI, RERA, and RDI scores and an elevation in serum serotonin levels. A previous proposal to consider estimation of serum Serotonin (5‐Hydroxytryptamine‐5HT) as a viable tool to diagnose OSA was reaffirmed from the results of this study. …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In accordance with the limitations of this study, the following conclusions were drawn: The overall incidence of OSA in elderly edentulous patients was found to be 40.94% (32.03% male, 8.91% female). An inverse correlation between OSA severity (as estimated by AHI, RERA, and RDI scores) and serum serotonin level was validated in this study. Use of complete dentures modified to function as MAD led to a reduction in AHI, RERA, and RDI scores and an elevation in serum serotonin levels. A previous proposal to consider estimation of serum Serotonin (5‐Hydroxytryptamine‐5HT) as a viable tool to diagnose OSA was reaffirmed from the results of this study. …”
Section: Discussionsupporting
confidence: 76%
“…The modified MAD positions the mandible forward during sleep, effects pharyngeal expansion, and thereby helps reduce the severity of OSA. OSA cannot be completely cured by using this device . The results of the present study revealed that the number of patients with mild OSA increased with time, whereas the number of patients with moderate and severe OSA significantly decreased.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Relating this to this study, it can be stated that this damage causes perinatal brain injury and leads to neurological dysfunction which, in turn, alters the homeostasis of the body and brings about reduced ventilatory control during sleep and subsequent collapse of the pharyngeal airway. Thus, the relation between OSA and neurocognitive dysfunction found in the present study has strong support from previous research based on the findings of earlier studies . All patients of this study cohort were rehabilitated with complete dentures, which were used as MAD during sleep at night, and the reduction in severity of OSA and cognitive dysfunction was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of a complete denture prosthesis modified for nocturnal use as a mandibular advancement device (MAD) has already been demonstrated . An increase in pharyngeal volume effected by this device has also been shown to effectively ameliorate OSA in edentulous patients …”
mentioning
confidence: 91%